The Non-Peptide Arginine-Vasopressin v1a Selective Receptor Antagonist, SR49059, Blocks the Rewarding, Prosocial, and Anxiolytic Effects of 3,4-Methylenedioxymethamphetamine and Its Derivatives in Zebra Fish - Ponzoni, Luisa; Braida, Daniela; Bondiolotti, Gianpietro; Sala, Mariaelvina (Frontiers in Psychiatry, 2017)
3,4-methylenedioxymethamphetamine (MDMA) and its derivatives, 2,5-dimethoxy-4-bromo-amphetamine hydrobromide (DOB) and para-methoxyamphetamine (PMA) are recreational drugs whose pharmacological effects have recently been attributed to serotonin 5HT2A/C receptors. However, there is growing evidence that the oxytocin/vasopressin system can modulate some the effects of MDMA. In this study, MDMA (2.5-10 mg/kg), DOB (0.5 mg/kg) or PMA (0.005, 0.1 or 0.25 mg/kg) were administered intramuscularly (IM) to adult zebrafish, alone or in combination with the V1a vasopressin antagonist, SR49059 (0.01-1 ng/kg), before carrying out conditioned place preference (CPP), social preference, novel tank diving and light-dark tests in order to evaluate subsequent rewarding, social and emotional-like behaviour. The combination of SR49059 and each drug progressively blocked: 1) rewarding behaviour as measured by CPP in terms of time spent in drug-paired compartment; 2) pro-social effects measured on the basis of the time spent in the proximity of a nacre fish picture and 3) anxiolytic effects in terms of the time spent in the upper half of the novel tank and in the white compartment of the tank used for the light-dark test. Antagonism was obtained at SR49059 doses which, when given alone, did not change motor function. In comparison with a control group, receiving vehicle alone, there was a 3-5 times increase in the brain release of isotocin (the analogue of oxytocin in fish) after treatment with the most active doses of MDMA (10 mg/kg), DOB (0.5 mg/kg) and PMA(0.1 mg/kg) as evaluated by means of bio-analytical reversed-phase high-performance liquid chromatography. Taken together, these findings show that the oxytocin/vasopressin system is involved in the rewarding, pro-social and anxiolytic effects of MDMA, DOB and PMA in zebrafish, and underline the association between this system and the behavioural alterations associated with disorders related to substance abuse.